ESG investment strategies and the financial performance of European agricultural companies: a new modelling approach - Cristea, Mirela; Noja, Grațiela Georgiana; Drăcea, Raluca Mihaela; Iacobuță-Mihăiță, Andreea-Oana; Dorożyński, Tomasz (Journal of Business Economics and Management, 2024)
This paper aims to appraise the impact of ESG credentials on the financial performance of agricultural companies with main headquarters in Europe by examining the strategic ESG investment behaviour of firms in twelve specific sectors. The methodology consists of a two-fold approach: first, cross-sectional FGLS regression with generalised least squares; second, overall interlinkages between considered variables through Bayesian network analysis. The research questions focus on the implications of each ESG pillar – environmental, social, and governance – on the performance of agricultural companies. Key findings entail that the environmental dimension strongly relates to agricultural companies’ outcomes, such as toxic chemicals reduction strategies, waste recycled to the total waste contribution, biodiversity impact reduction, and eco-design products. As regards the social pillar of ESG, salaries and wages positively relate only to shareholders’ earnings, while governance factors like CEO compensation, board structure type, and board’s gender diversity favourably influence the financial performance of agricultural companies. ESG implications for agricultural companies are beneficial when they implement sustainable strategies. These strategies include establishing targets for water efficiency policies, increasing employee turnover, maintaining a steadfast water efficiency policy, enhancing the use of environmentally-friendly products, and reevaluating board structures from unitary to two-tier or mixed types.First published online 2 January 2025